2020
DOI: 10.29045/14784726.2020.06.5.1.20
|View full text |Cite
|
Sign up to set email alerts
|

UK ambulance service resuscitation management of pulseless electrical activity: a systematic review protocol of text and opinion

Abstract: Background: Out-of-hospital cardiac arrest patients with pulseless electrical activity are treated by paramedics using basic and advanced life support resuscitation. When resuscitation fails to achieve return of spontaneous circulation, there are limited evidence and national guidelines on when to continue or stop resuscitation. This has led to ambulance services in the United Kingdom developing local guidelines to support paramedics in the resuscitative management of pulseless electrical activity. The conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This review was conducted in accordance with the Joanna Briggs Institute (JBI) for systematic review of text and opinion (9) according to a priori published protocol (10). The review is registered on the international prospective register of systematic reviews (CRD42019138731).…”
Section: Methodsmentioning
confidence: 99%
“…This review was conducted in accordance with the Joanna Briggs Institute (JBI) for systematic review of text and opinion (9) according to a priori published protocol (10). The review is registered on the international prospective register of systematic reviews (CRD42019138731).…”
Section: Methodsmentioning
confidence: 99%
“…Two recent systematic reviews of evidence-based guidelines (EBGs) in pre-hospital care found that they frequently vary in quality and have noticeable gaps in their methodology and adherence to reporting standards ( Fishe et al, 2018 ; Turner et al, 2020 ). Even less is known about the development and quality of the individual policies, guidelines and protocols that guide clinical practice and service delivery within the confines of each EMS organisation ( Coppola et al, 2020 ). Hence, there is a need to better understand the process involved in the development of these documents within EMS to avoid unwarranted variation in EMS clinical practice.…”
Section: Introductionmentioning
confidence: 99%